Healthy lifestyle is associated with lower infection incidence in type 2 diabetes: A prospective cohort study with multi-omics mediation analysis - Mingming Li; Haojun Zhai; Xiaoqiu Dai; Juan Ye; Xiaoqi Ye; Yebei Liang; Siyu Chen (BMC Medicine, 2026)
Abstract Background Individuals with type 2 diabetes mellitus (T2DM) are at substantially increased risk of infections, yet effective strategies for infection prevention remain limited. Although adherence to healthy lifestyles has been associated with lower infection risk in the general population, whether these benefits extend to individuals with T2DM remains unclear. Moreover, the association between the American Heart Association’s Life’s Essential 8 (LE8) metrics and infection risk has not been investigated. Therefore, this study aimed to evaluate associations between multidimensional lifestyle factors, Life’s Essential 8 (LE8) scores, and infection incidence rate in T2DM, and to explore underlying pathways using multi-omics mediation analysis. Methods This prospective cohort included 12,885 UK Biobank participants with T2DM (mean age 60.1 years; 30.6% female), followed for a median of 13.1 years. Exposures were adherence to a healthy lifestyle (smoking, BMI, diet, physical activity, sleep, alcohol) and LE8 score ( n = 9,164). The primary outcome was total incident infections, with pneumonia, gastroenteritis, and sepsis as secondary outcomes, ascertained from hospitalization and death registries. Multivariable negative binomial regression estimated associations as incidence rate ratios (IRRs) and 95% confidence intervals (CIs). Mediation analyses were conducted using nuclear magnetic resonance metabolomics ( n = 8,971; 325 biomarkers) and Olink proteomics ( n = 1,078; 2,920 proteins), with candidate mediators identified via false-discovery-rate-controlled screening and effects estimated using bootstrap methods.. Results Ideal lifestyle adherence was associated with a 44% lower infection incidence rate (IRR 0.56, 95% CI 0.46–0.68), with similar reductions for pneumonia and sepsis. Key protective factors included never smoking, healthy BMI, adequate sleep, and physical activity. LE8 scores showed dose-dependent associations, with each 5-point increase linked to an 11% lower risk (IRR 0.89, 95% CI 0.87–0.91). Mediation analysis highlighted lipid and fatty acid metabolism, including degree of unsaturation, HDL-related lipids, and GlycA. Proteomic mediators, including TRAIL-R2 and Galectin-9, implicated inflammation and innate immunity. Conclusions Maintaining an ideal lifestyle and higher LE8 scores was associated with lower infection incidence rate in T2DM, partly mediated by lipid metabolism and immune-inflammatory pathways.